Impaired visual decision-making in individuals with amblyopia - Farzin, Faraz (2011)
This study examined the effects of amblyopia on perceptual decision-making processes to determine the consequences of visual deprivation on development of higher-level cortical networks outside of visual cortex. A variant of the Eriksen flanker task was used to measure response time and accuracy for decisions made in the presence of response-selection conflict. Performance of adults with amblyopia was compared to that of neurotypical participants of the same age. Additionally, simple and choice reaction time tasks presented in the visual and the auditory modality were used to control for factors such as feature visibility, crowding, and motor execution speed. A selective deficit in response time for visual decisions was found when individuals with amblyopia used either the amblyopic or non-amblyopic (dominant) eye, and this deficit was independent of visual acuity, motor time, and performance accuracy. In trial conditions that provoked response-selection conflict, responses were significantly delayed in amblyopic relative to neurotypical participants, and were not subject to standard trial sequence effects. Our results indicate that, beyond the known effects of abnormal visual experience on visual cortex, suboptimal binocular input during a developmental critical period may also impact cortical connections to downstream areas of the brain, including parietal and frontal cortex, that are believed to underlie decision and response-selection processes.